Graph theory applications to deregulated power systems (2021)
In this chapter, we describe the setting for the problems of interest for the work presented in this book. We first introduce the background and the motivation of our research. Then, we present the scope of this report and highlight the major contributions if this work. We end with an outline the contents of the remainder of this chapter